The Effect of the Household Balance Sheet on Unemployment – Evidence from Spanish Provinces - Jonas Schlegel; Sebastian Watzka (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper takes a close look at one of the possible causes of Spain's severe crisis and studies the extent to which the increase in Spanish unemployment is due to the effects of household balance sheet effects. By estimating proxies for housing net worth shocks as well as household sector debt to disposable income ratios for 52 Spanish provinces together with detailed data on sectoral provincial unemployment data, we find that household balance sheet effects contribute a significant portion to the increase in unemployment between 2008 and 2010. Our outcomes confirm the results for the US from Mian and Sufi (2014). In contrast, for the time period between 2007 and 2014, we do not find any explanation power. Mostly interesting, we find contrary results for the episode between 2010 and 2014: Provinces, which cut back demand between 2007 and 2010 significantly strongly, did so significantly less than other provinces subsequently.
Keywords: G01; J23; E21; 330